ANALYZING PT. BANK KEB HANA INDONESIA HEALTH BEFORE AND AFTER MERGER USING RBBR APPROACH - Walakandou, Regina Joan Ribka; Lambey, Linda .; Tulung, Joy Elly (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Bank has important roles in stabilizing financial, inflation control, and driving the economy in a country. That is why a bank has to manage their performance by staying ‘healthy’ to support the economy in a country, and one way to assess bank health according to OJK is by using RBBR (Risk-Based Bank Rating) approach. One example of banks in Indonesia is PT. Bank KEB Hana Indonesia, who conducted a merger in 2014. This research aims to assess PT. Bank KEB Hana Indonesia health and to compare the health before and after merger. This research used quantitative descriptive approach to assess PT. Bank KEB Hana Indonesia health based on the RBBR approach that consists of RGEC factors; Risk Profile, GCG, Earnings by using NIM and ROA, and Capital by using CAR. The result shows that there is no major difference on RGEC variables and Bank Health of PT. Bank KEB Hana Indonesia before and after merger, since both periods were assessed as ‘very healthy’. It is suggested that PT. Bank KEB Hana Indonesia should improve their performance because there are still some weaknesses in the RGEC factors.Keywords: bank health, risk-based bank rating (rbbr) approach, risk profile, good corporate governance, earnings, nim, roa, capital, car, merger